Pemanfaatan lagu daerah nusantara sebagai media pembelajaran BIPA berbasis local indigenous - Ayu Wulandari; Zamzani Zamzani; Nurhadi Nurhadi (Jurnal Bahasa Indonesia bagi Penutur Asing, 2022)
BIPA is currently increasingly in demand by other nations. In addition to learning the language, BIPA students are also introduced to Indonesian culture. Indonesian culture is important and needs to be known by BIPA students so that they can understand well the cultures that exist in Indonesia. One of the BIPA learning media that can be used in learning the language and introducing Indonesian culture is through song. Indonesian songs can be in the form of an archipelago folk song that has many cultural values and moral messages or character values. This research is a descriptive study and the source of data in this study are folk songs of the archipelago. The form data is in the form of words that contain an introduction to basic vocabulary for BIPA learners. Data collection techniques are carried out by observing notes. The results of this study obtained a description of the archipelago's folk songs that can be used as Indigenous digital-based BIPA learning media. The folk songs of the archipelago include Soleram, Cut the Goose Duck, My Goats, Come on Mama, Injit-Injit Ants, and Ondel-ondel. The folk songs of the archipelago can be used as BIPA learning media for basic BIPA learners who are just at the stage of getting to know the basic vocabulary and getting to know Indonesian culture